TOEFL PREPARATION TRAINING PROGRAM TO ENHANCE STUDENTS’ TOEFL SCORE - Dwi Indra Aprilliandari; Prasetyawan Aji Sugiharto (Institut Pendidikan Tapanuli Selatan, 2023)
TOEFL is one method of measuring English competence and serving as a standard for anyone studying or speaking English as a foreign language. Because the TOEFL is a globally renowned language test that certifies one's English ability, there is a minimum score to achieve in order to complete a certain requirement, such as a support document to apply for a job, institution, or study abroad. It is challenging for almost all Indonesians to attain a minimum TOEFL score. The purpose of this article was to figure out the effectiveness of the TOEFL preparation training program in enhancing students' TOEFL score. This paper gathered information using action research, which consists of four steps: planning, implementation, observation, and reflection. The TOEFL training program was carried out four times a week for a month, including eight meetings for listening comprehension, ten meetings for structure and written expression, and ten meetings for reading comprehension. The class divided into three classes for each class consisting of 32 students. From the result, it can be seen that there is a significant improvement after the students participated in the TOEFL training program. It showed the students who reach score ≤400 in post-test more than in pre-test and the score increased as expected. On the pre-test, the students who got scores 400-500 was only 3% and after the training was given it increased became 13%. It can be concluded that TOEFL training program not only helps the students to improve their scores but also their comprehension of the TOEFL test